JUSTIFICATION OF THE SHELF LIFE OF FUNCTIONAL PRЕBIOTIC SEMI-PRODUCT - Slashcheva, Alina (Sworld-Us Conference proceedings, 2025)
It was determined that the recommended storage period of functional prеbiotic semi-product in hermetically packed parchment bags is 12 months at a temperature of 18…20°C and humidity not exceeding 70%. It was determined that during the specified storage p